THE REASONS AND ESSENCE OF POLICY OF FORCED RELOCATION OF PEOPLES TO THE UZBEKISTAN SSR - Mavluda Rakhmanova (Western European Studies, 2025)
The article examines the ethnic repressions carried out in the Soviet state on the eve of World War II and during it, the reasons and main content of the forced relocation of peoples by the Soviet government to the Uzbek SSR
Keywords: deportation; repression of the Soviet government; World War II; special settlements